Impact of a hybrid exercise intervention on subjective happiness and self-perceived health of workers: a case study - Núñez-Sánchez, José M.; Einsle, Carmen Sarah; López-Fernández, Jorge; Jiménez Díaz-Benito, Víctor (Frontiers in Sports and Active Living, 2025)
IntroductionPhysical activity-based workplace wellness programs (WPPA) are effective in improving health, well-being, and productivity among workers. Despite this, smaller organizations often face challenges in implementing these initiatives. This study assesses the effects of a structured hybrid exercise program, delivered by fitness centers, on subjective happiness, self-perceived health, and physical metrics in Spanish workers during the post-COVID period.MethodsA pilot study was conducted over three months with 44 participants (45.5% male, 54.5% female) who were sedentary or overweight. The program included a combination of online and in-person exercise sessions. Pre- and post-intervention data were collected using validated tools, such as the SF-36 for self-perceived health and the Subjective Happiness Scale. Statistical methods included paired t-tests and multivariate analyses.ResultsThe intervention led to significant improvements in subjective happiness (p = 0.034; d = 0.33) and several dimensions of self-perceived health, including vitality and general health (p < 0.01; d > 0.50). Overall physical and mental health scores showed moderate enhancements, reflecting the program's effectiveness.DiscussionThe findings demonstrate the potential of hybrid exercise interventions as a practical solution for promoting well-being and happiness in small and medium-sized enterprises that cannot afford to build workplace gyms.